Development of the services sector for the elderly working-age population - Khamraeva Sayyora Nasimovna; Ochilova Nargiza Akramovna (THE INNOVATION ECONOMY, 2026)
This article examines theoretical approaches to developing services for the working-age population, increasing their access to social infrastructure, and further improving their well-being. It also analyzes the opinions of economists on this issue and develops necessary proposals and recommendations.